Huddle : how women unlock their collective power - Baldwin, Brooke (Journalist) (Harper Business, an imprint of HarperCollinsPublishers, 2021)
"CNN news anchor Brooke Baldwin explores the phenomenon of "huddling," when women lean on one another--in politics, Hollywood, activism, the arts, sports, and everyday friendships--to provide each other support, empowerment, inspiration, and the strength to solve problems or enact meaningful change. Whether they are facing adversity (like workplace inequity or a global pandemic) or organizing to make the world a better place, women are a highly potent resource for one another."--